Is faster, better when teaching skills based management courses? : a comparison of compressed and full-term course delivery methods - Peter, Louis St.; Butler, Deborah S. (Economics and Business Review, 2011)
This study investigates students' self-perceptions of learning related to their participation in either a 3- or 15-week skill-based graduate coaching course. The results indicate students enrolled in the compressed course saw a significant increase in their coaching skills from pre-test to post-test; students enrolled in the full-term did not see the same statistically significant increase. Further, students in the compressed course had statistically significant higher counseling and challenging skills than the full-term students. These findings are relevant to the debates surrounding the benefits accrued from obtaining an MBA. (original abstract)